Integrating natural resource potential and technological innovation: An interdisciplinary study on the development of seaweed-based bioplastics in indonesia as an alternative to conventional plastics - Qiswian, Chesa Helsin (Institute for Advanced Science, Social, and Sustainable Future (IASSSF), 2025)
Background: Plastic usage has become an integral part of modern life, spanning applications from food packaging and single-use bags to large-scale industrial uses. With plastic waste ranking as the second largest type of waste in Indonesia—and with Indonesia identified by a Nature journal (9 September 2024) as the world’s third largest contributor of plastic pollution at 3.4 million metric tons per year—the environmental impact is significant, especially considering plastic's persistence for hundreds to thousands of years. Methods: This research employs a qualitative approach, analyzing relevant literature, policy documents, and industry reports to assess the opportunities and challenges in developing bioplastics made from seaweed in Indonesia. Findings: he study finds that seaweed-based bioplastics, which are naturally degradable within four to six weeks and even edible, offer a promising alternative to conventional plastics. Indonesia’s position as the second-largest seaweed producer globally presents a unique opportunity to harness social, economic, and environmental benefits. However, challenges remain in scaling sustainable seaweed aquaculture, adopting efficient technologies, and formulating supportive policies, with international cooperation in knowledge and technology transfer deemed essential. Conclusion: The development of seaweed-based bioplastics in Indonesia could serve as a sustainable solution to the plastic waste crisis, provided that targeted research, policy reforms, and industry collaborations are implemented. Novelty/Originality of this article: This research uniquely integrates environmental, economic, and social perspectives to advance the emerging field of seaweed-based bioplastics, highlighting the potential for international partnerships to drive sustainable innovation in Indonesia.